International experimentations. The debate on placebo-controlled studies - Torlone, Gaetano (Medicina e Morale, 2004)
The starting point of the present work is an article by P. Lurie and S.M. Wolfe published in the New England Journal of Medicine in 1997. In this article the authors showed some trials on short regimen of AZT in perinatal transmission of Hiv that they accuse of being unethical. These studies were sponsored by western organizations and carried out in some sub-Saharian African and Asian countries. The most important ethical question pointed out was the use of a placebo-controlled arm even if the Zidovudine were already used as standard therapy for the reduction of the perinatal transmission of HIV, after a randomized controlled trials performed in Usa and France that proved its effectiveness. In the first part of the article international literature in the five-years period before and after the publication by Lurie and Wolfe is analyzed. A statistically significant increment in publications on ethics of clinical research in developing countries in the last period is shown. In the second part of the work the subject of ethical justification of the placebo-controlled arm use in developing countries when a standard therapy is known is analyzed. Pros and cons are explained basing our analysis especially on interpretative categories by A.J. London. The conclusions suggest that this clinical trial design, in such conditions, is not ethically and logically sound. Nevertheless the rightfulness of the trial results transferability between populations with different historical and cultural identities is yet under discussion.